Effect of shape deprivation on retinal thickness in myopic mice using an OCT method - Duan, Ming-Ming; Liu, Hui; Zhong, Yu-Lin (Frontiers in Neuroscience, 2023)
Abstract Purpose: The purpose of this study was to study in retina (R) thickness changes in myopic mice using optical coherence tomography (OCT). Methods: There were 18 mice in the form-deprivation myopia (FDM) group，in which the left eye was not treated as a control;18 untreated mice served as a normal control group. The diopter of all mice was measured 21 days after birth (P21), before form deprivation. After 4 weeks of form deprivation (P49), the refraction, fundus, and retinal sublayer thickness of all mice were measured. Results：After 4 weeks of form deprivation, the refractive power of the right eye in the FDM group was significantly higher than that in the left eye (P <0.05). There was no significant change in the refractive power of the left eye in the FDM group compared with the normal control group. The R, nerve fiber layer (NFL), inner nuclear layer (INL), and outer nuclear layer (ONL) in the right eye of the FDM group were significantly thinner than those of both the FDM and control groups (P <0.05). There was no significant change in photoreceptor (PR). Conclusion: Our study highlights that the myopic mice have decreased R thickness, which might reflect the potential pathological mechanism of myopia.